TRENDS IN HR MANAGEMENT AT THE ENTERPRISE - Svitlana Babych; Dmytro Babych (Соціальна економіка)
The purpose of this article is to assess the possibility of introducing new approaches to personnel management into domestic practice. Summarizing the results of the study, we can note the following: there is a discrepancy in the study of HR management issues in domestic scientific works and foreign scientific thought. Recent studies by Ukrainian scholars are related to the assessment of international experience in HR practices, adaptation of domestic HR systems to external challenges (war, pandemic, etc.). Foreign works are devoted to the disclosure of the theoretical and practical foundations of the application of new HR practices, empirical research of the effectiveness and efficiency of their implementation, and case studies. In the light of the trend in HR management to take into account the interests of the employee and ensure his/her well-being, the following newest HR practices have been selected for implementation in domestic enterprises: personalized human resource management; management practices based on corporate social responsibility; HR co-creation; Agile HR. Among the disadvantages and problems of applying personalized human resource management is the lack of time and personnel in the HR department to select an individual management strategy for each employee if the company is medium or large in size. The difficulty of assessing employee well-being can be an obstacle to implementing the principles of corporate social responsibility in human resources management. It is necessary to take a balanced approach to the formation of a system of direct and indirect indicators of employee satisfaction to obtain a true assessment. A rather patriarchal society, which is characterised by top-down implementation of innovations rather than the design of new HR management practices with the involvement of outsiders, may be an obstacle to the introduction of HR co-creation approaches. The main obstacle to the introduction of Agile HR may be the reluctance to change the organisational structure of HR management, as well as the reluctance of staff to abandon template solutions. Prospects for further research in the subject of this article are related to the assessment of the readiness of domestic enterprises to introduce innovations in the field of HR management.